MASS MEDIA DI ERA MODERNITAS: STUDI TAYANGAN SINETRON RELIGIUS - Muhammad saleh (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2015)
The information era and modernity reconstruct attitudes and behaviours of comsumer mass media, especially TV, generations are bad morally because of media exposure that is so strong, so the writer tried to lift the title above to reconstruct the nation's morality, makes the ethics of broadcasting and movies that didn’t forbidden by islam as solution. The method used in this paper is a descriptive with theory of agenda setting and CDA.